Theurgy, Paredroi, and Embodied Power in Neoplatonism and Late Antique Celestial Hierarchies - Katarina Pejovic (Religions, 2024)
This article will place the rituals of the Greek Magical Papyri (PGM) for the acquisition of a supernatural assistant (paredros) into conversation with broader late antique debates surrounding the place of daimones within the celestial hierarchy. In considering the writings of Plotinus, Plutarch, Porphyry, and Iamblichus, it will survey points of contention surrounding questions of appropriate and inappropriate displays of ritual power, as facilitated by intermediary spirits who act as intercessors between humanity and the divine. Through analyzing the metaphysical underpinnings of the nature of the paredros, as variously articulated within the rituals for their conjuration within the Greek Magical Papyri, it will contextualize the aims of the ritualist against the backdrop of Iamblichus’ theurgy in pursuit of mastery of—and intimate, transcendent communion with—the fundamental numinous nature of the world. In doing so, this article argues that Iamblichus’ theurgy and the paredros rituals of the PGM ultimately grasp towards similar soteriological goals using different ritual methodologies; both seeking to elevate the incarnated body of the ritualist into a higher level of spiritual attainment through direct confrontation with the powers of nature.